WORDS, RHYTHM AND MEANING: LANGUAGE AND HYBRIDITY - El Samad, Soha (European Scientific Journal, ESJ, 2014)
The subversion of Western epistemological ideas and the problem of identification have been major concerns of postcolonial theory and writers. However, the extent to which postcolonial writers succeed in their endeavor to write back to the episteme is largely determined by the effectiveness of the language or their discourse. This paper deals with how language as used by postcolonial writers can unintentionally reveal a deeper or different meaning from their initial aims of answering back to an â€˜Otherâ€™ culture that has labeled them as uncivilized and inferior. The heterogeneity of their language reveals contradictions and also points to the development of a hybridity capable of coping with a postcolonial identity crisis. In the course of this study that includes texts by Chinua Achebe and Wole Soyinka, the native discursive medium of Tayeb Salihâ€™s novella, Season of Migration to the North, would also be analyzed for gaps, silences, and contradictions. A Kristevan semanalysis is applied to draw attention to the fluidity of the language, the repressed unconscious, and the semiotic disposition of the novelists and protagonists. Hence, these novels can offer a practical demonstration of how language can reveal the â€œindistinct musicâ€ and meaning of authorsâ€™ memories to produce texts whose originality lies in their diversity.